SEASONAL FLUCTUATIONS IN THE SURFACE SALINITY OFF THE NORTH COAST OF JAVA - Soeriaatmadja, Raden E. (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1956)
The division of the region investigated according to P. CH. VEEN is redescribed. The micro salinity titration by means of the method described by G. H. ARNOLD with an accuracy of 0.1 ? was used for this investigation. This technique was adopted because of the large number of observations, and was sufficiently accurate since salinity in these waters varies widely. The annual range in salinity is large, caused by a considerable discharge of fresh water from the many big and small rivers, especially in the rainy-season as well as by the inequality of salinity of the oceanwaters coming from the East, and the South China Sea water coming from the West, during the dry and wet-sason respectively. In the east-monsoon, the eastern section is covered with ocean water over 34.0 ? and the western section with mixed waters ranging between 31.5 ? and 34.0 ?, while in the west-monsoon, the area is covered with mixed water less than 32.5 ?.